1998
DOI: 10.1002/(sici)1097-4598(199808)21:8<1089::aid-mus18>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on nerve conduction parameters in carpal tunnel syndrome

Abstract: Correction factors exist to allow for the dramatic effect that temperature has on nerve conduction study parameters. However, these are based on normal nerves in normal individuals and may not be appropriate in the diseased nerve setting. Our clinical study showed that in carpal tunnel syndrome, the median nerve reacts differently to temperature changes compared with normal ulnar controls. Furthermore, statistically significant differences exist between the rates of change with increasing temperature in motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…As in the study by Lee et al,13 considerable variability was found in distal latency, which may be a function of temperature in the distal extremity, with temperature being directly proportional to conduction velocity 2, 5. Cooling of the nerve in normal subjects prolonged latency with either no change or a slight increase in amplitude, and never resulted in loss of SNAP.…”
Section: Discussionmentioning
confidence: 65%
“…As in the study by Lee et al,13 considerable variability was found in distal latency, which may be a function of temperature in the distal extremity, with temperature being directly proportional to conduction velocity 2, 5. Cooling of the nerve in normal subjects prolonged latency with either no change or a slight increase in amplitude, and never resulted in loss of SNAP.…”
Section: Discussionmentioning
confidence: 65%
“…All subjects underwent a brief clinical examination by a physician (HS or ME) 1 In order to ensure an adequate hand temperature and minimize temperature as a source of error (Haler et al 1983;Ashworth et al 1998), the determination of conduction velocity was preceded by a bicycle ergometer test which has been shown to stabilize skin temperature around 34°C (Sande´n et al 2005). The temperature was measured at the tip of the fourth finger.…”
Section: Methodsmentioning
confidence: 99%
“…Halar et al (1983) suggested a median sensory nerve correction of 1.4 m/s per 1°C and an ulnar nerve correction of 1.6 m/s, but only when skin temperatures were <29.6°C. The effect of temperature on nerve conduction seems less pronounced in diseased nerves, most notably as the skin is warmed (Ashworth et al 1998;Wu et al 1993). Ashworth et al (1998) described a 0.11-m/s increase per 1°C for median nerves affected by CTS, in contrast to a 1.0-m/s increase per 1°C on the presumably healthy ipsilateral ulnar nerve.…”
Section: Nerve Conduction and Skin Temperaturementioning
confidence: 99%
“…The observations of Ashworth et al (1998) on reduced temperature effect in diseased nerves might be relevant to this population. Median nerve wrist-palm SNCV showed less then half the temperature effect of the ipsilateral ulnar nerve segment.…”
Section: Nerve Conduction and Skin Temperaturementioning
confidence: 99%